DOI: 10.18174/458202
|View full text |Cite
|
Sign up to set email alerts
|

Environmental tuning of the genetic control of seed performance : a systems genetics approach

Abstract: Environmental tuning of the genetic control of seed performance: a systems genetics approach, 214 pages.PhD thesis, Wageningen University, Wageningen, the Netherlands (2018) With references, with summary in English

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 351 publications
0
7
0
Order By: Relevance
“…For example, we analysed the correlation of the flowering time in a long day (FTLD) phenotype QTL of a Bay x Sha RIL population (Joosen et al 2012) with eQTLs from experiments using the same population in (Figure 4.4). We selected the top five correlated genes and found that an FLC eQTL profile on dry seed (Serin 2018) has the highest Spearman correlation coefficient (0.86) with the phenotype QTL. FLC is highly abundant in dry seeds to regulate temperature-dependent seed germination (Chiang et al 2009).…”
Section: Use Case 3: Correlation Between Phenotype and Gene Expressio...mentioning
confidence: 99%
See 4 more Smart Citations
“…For example, we analysed the correlation of the flowering time in a long day (FTLD) phenotype QTL of a Bay x Sha RIL population (Joosen et al 2012) with eQTLs from experiments using the same population in (Figure 4.4). We selected the top five correlated genes and found that an FLC eQTL profile on dry seed (Serin 2018) has the highest Spearman correlation coefficient (0.86) with the phenotype QTL. FLC is highly abundant in dry seeds to regulate temperature-dependent seed germination (Chiang et al 2009).…”
Section: Use Case 3: Correlation Between Phenotype and Gene Expressio...mentioning
confidence: 99%
“…Finnegan et al (2020) showed that the activation of FLC expression is started during embryo development and continues until the vegetative stage. In the transcriptome analysis of dry seed of Bay x Sha RILs (Serin 2018), FLC is expressed and shown to be regulated by two eQTLs (Figure 4.4). eQTL on chromosome 5 is collocated with the gene location, which is a likely cis-eQTL (e.g., variation in promoter leading to variation in gene expression).…”
Section: Chaptermentioning
confidence: 99%
See 3 more Smart Citations